2017
DOI: 10.29027/ijirpem.v1.i1.2017.9-16
|View full text |Cite
|
Sign up to set email alerts
|

Quotient-3 Cordial Labeling for Some Unicyclic Graphs –Part-II

Abstract: Let G be a graph of order p and size q. Let

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The cordial labeling concept was first introduced by cahit [2]. The quotient-3 cordial labeling have been introduced by P. Sumathi, et al found in [3][4][5][6]. They found some family of graphs are quotient-3 cordial.…”
Section: Introductionmentioning
confidence: 99%
“…The cordial labeling concept was first introduced by cahit [2]. The quotient-3 cordial labeling have been introduced by P. Sumathi, et al found in [3][4][5][6]. They found some family of graphs are quotient-3 cordial.…”
Section: Introductionmentioning
confidence: 99%
“…The cordial labeling concept was first introduced by cahit [1]. The quotient-3 cordial labeling have been introduced by P. Sumathi, A. Mahalakshmi and A. Rathi found in [8][9][10][11][12]. They found some family of graphs are quotient-3 cordial.…”
Section: Introductionmentioning
confidence: 99%
“…The cordial labeling concept was first introduced by cahit [1]. The quotient-3 cordial labeling have been introduced by P. Sumathi, A. Mahalakshmi and A. Rathi found in [5][6][7]. They found some family of graphs are quotient-3 cordial.…”
Section: Introductionmentioning
confidence: 99%